The Caribbean Low-Level Jet: relationship with climate and weather in Central America - Maldonado Mora, Tito José (2013)
Central America and the Caribbean region is conformed by countries and islands among the poorest of the Americas and even of the world. Many of their inhabitants are living in prone areas to natural disasters. It has been highlighted that most of the natural disaster reports in the last years, have been related to hydro-meteorological phenomena. Indeed, it is well known that this region is constantly affected by a wide variety of meteorological events, such as traveling easterly waves, tropical cyclones, convective systems, cold surges coming from the northern hemisphere, the mid-summer drought (MSD), the warm pools, the trades, and an intense low-level jet over the Caribbean Sea. It should be understood that variations in the intensity of these elements in combination with the social factors (i.e. people living in risky areas), can increase the probability to suffer natural disasters. In that sense, within the framework of the Center for Natural Disaster Science (CNDS), the present essay reviews the current knowledge on one of the most striking climate features of the region, the Caribbean low-level jet (CLLJ). It has been found in the literature some mechanisms explaining its origin, maintenance, and structure, nevertheless more studies using modeling techniques and observations are required in order to validate such mechanisms. It is known that the large-scale convergence (divergence) at the jet exit (entrance) is associated with precipitation patterns in the Central American isthmus. It was found that discrepancies calculating precipitation in the General Circulation Models (GCMs) and reanalysis lead to a misrepresentation of the climate in this region, and these discrepancies are hand-to-hand with errors in the models estimating the low-level wind flow. Moreover, some studies highlighted the association of the CLLJ with the vertical wind shear (VWS), as a main mechanism of control, and the influence of the VWS on hurricanes and tropical cyclones. Furthermore, the influence of the large-scale climate modulators such as El Niño (ENSO), the North Atlantic Oscillation (NAO), the Madden-Julian Oscillation (MJO), upon the intensity of the jet have been related with changes in precipitation, sea surface temperatures (SST) anomalies in the Caribbean Sea, and tropical cyclone genesis. In spite that the jet has been identified as an important mechanism modulating the precipitation regime in Central America, the association with extreme phenomena such as droughts and/or heavy rain events is still not understood